TAFSIR AYAT-AYAT KONSUMSI DAN IMPLIKASINYA TERHADAP PENGEMBANGAN EKONOMI ISLAM - Kasdi, Abdurrohman (EQUILIBRIUM, 2013)
All economic activity originated from human physical needs in orderto survive in this world. All purposes to survive desperately sought his own will,but if the needs to survive cannot be met by himself, so he has to take the socialinteraction in fulfilling his needs of life. This interaction represents the economic interactions including of demand and supply, consumption and production. Islamexplained that the earth and everything in it is the mandate of God to human inorder to be used as well as possible for the prosperity and welfare. Islam alsoteaches human to apply the economic activities in order to gain the pleasure ofAllah in its function as the caliph in this world.